Effects of goat milk fractions on the stability of IGF-I in simulated gastrointestinal conditions. (May 2018) - Zhang, Fuxin; Xu, Lianying; Chen, Si; Wang, Bini; Shao, Yuyu; Zhao, Aiqing; Han, Xue
Abstract: The effects of goat milk fractions on the stability of insulin-like growth factor I (IGF-I) digested in the simulated gastrointestinal juice in vitro were investigated. IGF-I concentration was analyzed using an immunological sandwich-type ELISA method. The results showed that the concentration of pure IGF-I in simulated gastrointestinal juice decreased rapidly with the increasing digestion time. However, IGF-I in goat milk was more stable than pure IGF-I either in simulated gastric or intestinal juice. Goat milk and whey and whey supernatant fractions all effectively inhibited the proteolytic degradation of IGF-I in both the simulated gastric and intestinal juices. Dietary derived protease inhibitors, such as soya bean trypsin inhibitor (SBTI), lima bean trypsin inhibitor (LBTI) and egg white protease inhibitor (EWPI) all prevented IGF-I degradation in the simulated gastrointestinal juice, but the whey supernatant fraction represented more effective inhibition than the inhibitors. These results suggested that the whey supernatant fraction might contain specific inhibitors that protect IGF-I from the proteolytic degradation in the simulated gastrointestinal conditions, which was further verified by SDS-PAGE. Therefore, the whey supernatant fraction in goat milk could be a potential resource for the development of the effective oral IGF-I-based products. Highlights: Pure IGF-I degraded rapidly in the simulated gastric or intestinal juice. Goat milk is rich in IGF-I, especially whey and whey supernatant fractions. Whey supernatant fraction showed effective inhibition on the degradation of IGF-I.